2021
DOI: 10.1186/s40795-021-00475-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of under-nutrition during pregnancy on low birth weight in Tigray regional state, Ethiopia; a prospective cohort study

Abstract: Background Under-nutrition during pregnancy affects birth outcomes and neonatal outcomes. Worldwide, 20.5 million children were low birth weight, mainly in poor countries. However, there is no longitudinal-based evidence on the effect of under-nutrition during pregnancy on birth weight in Tigray regional state. Therefore, this study aimed at investigating the effect of under-nutrition during pregnancy on low birth weight in Tigray regional state. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…In contrast to this, our study showed that 48.6% of women avoided nutritious foods (dairy products, meat, egg, honey, vegetables and fruits) during their pregnancy. This could result in preterm birth and low birth weight 26 27. This finding was higher than the findings of the studies conducted in a Gurage zone, Amhara and Afar regions 3 17 22 23 while lower than a study conducted in Wonago town 20…”
Section: Discussionmentioning
confidence: 73%
“…In contrast to this, our study showed that 48.6% of women avoided nutritious foods (dairy products, meat, egg, honey, vegetables and fruits) during their pregnancy. This could result in preterm birth and low birth weight 26 27. This finding was higher than the findings of the studies conducted in a Gurage zone, Amhara and Afar regions 3 17 22 23 while lower than a study conducted in Wonago town 20…”
Section: Discussionmentioning
confidence: 73%
“…After a full‐text review, 42 studies were excluded for several reasons, including lack of full text, being outside the scope of the study, not presenting outcome measures, having different reference categories, and a high risk of bias. After a thorough review, 13 articles for the association between inadequate dietary diversity and anemia (Abriha et al, 2014; Agbozo et al, 2020; Ayensu et al, 2020; Delil et al, 2018; Deriba et al, 2020; Gibore et al, 2021; Jugha et al, 2021; Lebso et al, 2017; Ngimbudzi et al, 2021; Samuel et al, 2020; Vanié et al, 2021; Zerfu et al, 2016, 2019) and nine articles for determining the strength of the association between inadequate dietary diversity and low birth weight (Adem et al, 2020; Ahmed et al, 2018; Alemu & Gashu, 2020; Bekela et al, 2020; Berhe et al, 2021; Girma et al, 2019; Quansah & Boateng, 2020; Saaka et al, 2017; Zerfu et al, 2016) were included in the final meta‐analysis (Figure 1). One study was discarded after quality assessment (Vanié et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Second, despite the existing evidence on the association between maternal dietary diversity and geographical and socioeconomic variations among countries, subgroup analysis at the regional (Africa) level has not been reported (Gete et al, 2020). In addition, several new observational studies with inconsistent results, not included in previous reviews, have emerged in recent years (Adem et al, 2020; Berhe et al, 2021; Girma et al, 2019). Finally, we examined an additional outcome variable, maternal anemia, which correlates with dietary diversity and low birth weight (Figueiredo et al, 2018; Rahman et al, 2016; Rahmati et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nutrition is an important concern in pregnant women as it determines the quality of growth and development of the foetus and greatly affects birth and neonatal period 3,4 .…”
Section: Introductionmentioning
confidence: 99%